1993
DOI: 10.1136/pgmj.69.817.856
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic factors in Wegener's granulomatosis

Abstract: Summary:We analysed data from 64 patients with Wegener's granulomatosis to determine predictor variables of outcome. The mean period of observation after the diagnosis had been established was 3.2 (range 0.1-11.2) years. At the time of diagnosis, 15 (23%) patients had only local symptoms. The disease was generalized to multiple organs in 49 (77%) patients. Renal biopsies were obtained in 33 patients; 13 (39%) had extracapillary glomerulonephritis, which was the most common renal lesion. All but three patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
12
1
1

Year Published

1995
1995
2010
2010

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 11 publications
1
12
1
1
Order By: Relevance
“…The results of our analysis show that serum creatinine at diagnosis was a strong predictor of renal outcome: patients with These results are consistent with earlier findings [3][4][5][6]11], but indicate that the creatinine cutoff point associated with poor outcome may be lower than hitherto suspected. Previous reports mentioned cutoff points of 160 [5], 170 [11], and 310 μmol/L [18].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The results of our analysis show that serum creatinine at diagnosis was a strong predictor of renal outcome: patients with These results are consistent with earlier findings [3][4][5][6]11], but indicate that the creatinine cutoff point associated with poor outcome may be lower than hitherto suspected. Previous reports mentioned cutoff points of 160 [5], 170 [11], and 310 μmol/L [18].…”
Section: Discussionsupporting
confidence: 93%
“…Previous studies [5,14,15] showed that patients with generalized WG had shorter life expectancies than patients with limited disease. Increased mortality rates may be related to disease extent and severity and to increased treatment-related morbidity due to higher cumulative doses of CYC and CS.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Our patient had multiple organ involvement. Renal disease or impaired renal function, pulmonary involvement, advanced age, anemia and initial white blood cell count over than 10,000/Ìl are reported to be bad prognostic factors [19][20][21][22][23].…”
Section: Discussionmentioning
confidence: 99%
“…Среди возмож-ных причин возникновения ГВ наиболее вероятным считают микробный или вирусный фактор [8]. Заболе-вание нередко возникает после ОРВИ, переохлаждения, вакцинации, антибиотикотерапии, но может развиваться и у совершенно здоровых людей [3,7]. Вследствие пря-мого воздействия этиологического фактора формируется чужеродный антиген или аутоантиген, которые вызывают клеточный или гуморальный иммунный ответ.…”
unclassified